Hubungan antara Profil Elektrofisiologi dan Risiko Kejadian Kardiovaskular: Sebuah Tinjauan Sistematis: Analisis - Muhammad Haris Firdaus; Mirza Alfiansyah (Cermin Dunia Kedokteran, 2025)
Introduction: Cardiovascular diseases (CVDs) are the leading cause of death, accounting for 31% of global mortalities. This systematic review explores the role of electrophysiological profles in cardiovascular prevention, focusing on their integration into risk management protocols. Methods: A comprehensive review was conducted using the PubMed database, adhering to PRISMA guidelines. Of the 1,050 identifed studies, 10 met the inclusion criteria and were assessed for quality using the STROBE method. Results: Key electrophysiological markers were identifed as signifcant predictors of cardiovascular events. Abnormalities in Holter monitoring, such as a turbulence slope (TS) ≤25 ms/RRI, are strongly correlated with sudden cardiac death (HR 4.7). Prolonged QT intervals in ECG were linked to increased mortality from cardiac arrest (HR 2.4) and heart failure (HR 1.74). ST-segment depression during exercise stress testing was a strong predictor of coronary heart disease death (HR 2.47), especially during the recovery phase (HR 4.01). Discussion: Electrophysiological markers like Holter monitoring, ECG fndings and exercise stress testing are valuable for identifying high-risk individuals. Their integration into routine screening could improve early detection and prevention strategies, further research is needed to standardize protocols.